Influence of flagella and their property on the initial attachment behaviors of bacteria onto plastics. (1st March 2023) - Zhang, Mengya; He, Lei; Qin, Jianmei; Wang, Shuai; Tong, Meiping
Highlights: Flagella, especially sticky flagella, facilitate bacterial attachment onto plastics. Flagella help bacteria move fast, pierce energy barrier and attach onto plastics. Flagella help bacteria form more rigid attachment layer on plastic. Larger attachment of flagellar bacteria than cells without flagella in river water. HA mitigate the impact of sticky flagella via decreasing adhesive force. Abstract: Flagella and their property would influence the initial attachment of bacteria onto plastics, yet their impacts have not been investigated. In present study, four types of E. coli with or without flagella as well as with normal or sticky flagella were utilized to investigate the effects of flagella and their property on the initial attachment behaviors of bacteria onto six types of plastics in freshwater systems. We found that E. coli with flagella exhibited better initial attachment performance onto all six types of plastics than strain without flagella. Flagella could help bacteria swim near to plastics, pierce the energy barrier, and subsequently attach onto plastics. With stronger adhesive force, sticky flagella could further facilitate bacterial attachment onto plastics. Moreover, flagella especially sticky flagella could help bacteria form more rigid attachment layer on plastics. Even with humic acid in suspensions or in river water, flagellar E. coli showed greater attachment onto plastics than E. coli without flagella. Humic acid might adsorb onto sticky flagella and thus decreased the attachment of bacteria with sticky flagella onto plastics. Obviously, flagella as well as their property would impact the initial attachment of bacteria onto plastics and the subsequent formation of plastisphere in freshwater. Graphical abstract: Image, graphical abstract